PRODUKSI PAKAIAN BERDASARKAN LEMBAR BIAYA & TARGET HARGA RITEL - Susi Hartanto (LPPM Institut Desain dan Bisnis Bali, 2021)
Through a 3-year community service scheme (6 periods), 4 periods have been conducted. There are 3 stakeholders in this program: study program, community research partner, and brand partner. Along the process, community service partner has understood and be able to collaborate using digital method to produce clothing collections for brand partner. But although the stitching quality is well, cost prices are mostly found too high, not suitable for brand partner’s retail prices. Through this community service period, the aims are: 1) to train cost sheet making for each sku made; 2) to provide knowledge of target retail price and its calculations; 3) to provide knowledge on many components of clothing costs, including margin fees on multiple fashion platforms in Indonesia. This period is the last step of training and focus more on production and business mindsets before letting community service partner to go independent in the last period.